Algoritma Improved Symbiotic Organism Search (I-SOS) sebagai Pendukung Keputusan dalam Penentuan Dosen Pengampu Matakuliah - Zulkarnaen; Herman Budianto; Hendrawan Armanto (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
This study discusses the allocation of lecturers to apply courses by applying the concept of heuristic optimization using the Improved Symbiotic Organism Search (I-SOS) algorithm. The I-SOS Algorithm is a development of the previous algorithm, the Symbiotic Organism Search Algorithm, which is one of the latest metaheuristic methods inspired by the behavioral interactions seen between organisms in the universe. Optimizing the allocation of lecturers is very influential on the preparation of class schedules because scheduling a good course must be able to meet the needs of the parties directly related to the scheduling process. Conventional methods used today often cause problems in terms of efficiency and accuracy, imbalance of teaching load and inaccuracy in lecturer assignments requiring lecturers to take courses not in accordance with their interests and expertise.